Tổng hợp vật liệu CdS nano và hoạt tính xúc tác quang dưới ánh sáng khả kiến - Nguyễn Thị Việt Nga; Nguyễn Thị Kim Diễm; Trần Đình Thịnh; Nguyễn Bích Nhật; Trần Châu Giang; Huỳnh Thị Minh Thành; Nguyễn Văn Kim (My University, 2021)
Tổng hợp vật liệu CdS nano và hoạt tính xúc tác quang dưới ánh sáng khả kiến
Keywords: CdS nano